2004
DOI: 10.1177/0363546503260749
|View full text |Cite
|
Sign up to set email alerts
|

Initial Fixation Strength of Flexible All-Inside Meniscus Suture Anchors in Comparison to Conventional Suture Technique and Rigid Anchors

Abstract: The menisci are mobile joint surfaces, and they cover approximately 70% of the tibial plateau. 20 They play an important role in the load transmission, shock absorption, lubrication, passive stabilization, and load transmission of the knee. 20,21,34,36 Several clinical long-term studies have shown that total or partial meniscectomy may lead to cartilage degeneration and osteoarthritis. 18,22,45 When faced with these detrimental effects of meniscectomy, the desire to preserve the menisci is easy to understand.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 46 publications
5
53
1
2
Order By: Relevance
“…5,9,17,35,78,80,81 Vertical sutures are superior to both horizontal sutures and meniscus arrows in mean load-to-failure values. 4,16,52,78 The superior strength of vertical sutures is hypothesized to be due to the perpendicular orientation to the circumferential collagen bundles of the meniscus.…”
Section: Operative Techniquesmentioning
confidence: 99%
“…5,9,17,35,78,80,81 Vertical sutures are superior to both horizontal sutures and meniscus arrows in mean load-to-failure values. 4,16,52,78 The superior strength of vertical sutures is hypothesized to be due to the perpendicular orientation to the circumferential collagen bundles of the meniscus.…”
Section: Operative Techniquesmentioning
confidence: 99%
“…Des Weiteren kam es durch Wanderung der Implantate zu Weichteilirritationen, die in einigen Fällen sogar zu Läsionen an Nerven und Gefäßen führten [15]. Biomechanische Studien haben gezeigt, dass die Innen-Innen-Meniskusrefixationssysteme konventionellen Nahttechniken hinsichtlich ihrer Primärstabili-tät deutlich unterlegen sind [30,31]. Ein weiterer gravierender Nachteil von Innen-Innen-Refixationssystemen sind deren hohe Kosten.…”
Section: Figureunclassified
“…In addition, soft-tissue irritation may occur due to migration of the implants and has even caused lesions of the nerves and vessels in some cases [15]. Biomechanical studies have shown that the all-inside meniscal repair systems are clearly inferior to conventional suture techniques with regard to their primary stability [30,31]. Another serious disadvantage is the great expense of the all-inside repair systems.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations